Clinical aspects of functional foods and nutraceuticals [ - Ghosh, Dilip Kumar; Konishi, Tetsuya (CRC Press, 2015)
In the last three decades, revolutionary achievements have taken place in nutraceutical and functional food research including the introduction of a number of cutting-edge dietary supplements supported by human clinical trials and strong patents. Novel manufacturing technologies including unique extraction processes, bioavailability improvements through delivery technologies such as nanotechnology, and innovative packaging have been critical steps for their successful positioning in the marketplace and consumer acceptance worldwide. Nonetheless, mixed messages have emerged from